“You never know who’s watching”: how technology is shaping practice for social service professionals - Clary, Pamela Carlson (Kansas State University, 2014)
The purpose of this qualitative study was to examine the phenomenon of social networking sites (SNSs) and its impact on practicing human service professionals. In this exploratory study, 33 interviews, comprised of family life educators and social workers, were conducted in order to gain the perspective of how SNSs were being used in practice. A phenomenological approach was used to get at the lived experiences of these professionals. In addition, a Johari Window lens provided a way to understand the level of transparency professionals had when interacting with the digital culture. Themes found described how SNSs were being utilized in practice. These centered on benefits to the agency, clientele, and to the professional. The changing technological climate was shown to be impacting the delivery of services, yet professionals were underutilizing SNSs in practice. Regardless if the professional was on or offline, being recognized as a professional was extremely important. As a result, professionals were cognizant of potential consequences of using SNSs for professional and personal use. This awareness not only led professionals to want to safeguard their privacy, but also provided an opportunity for these professionals to develop guidelines for ethical digital behavior. Implications for research include exploring how a person’s digital status should be defined, if at all, how do privacy and ‘connecting’ influence each other, and what is the impact of viewing others’ posts on the ego strength of the person. The biggest implication for practice was the need for specific policies designed around professional digital behavior. In the absence of specific guidelines, professionals established their own set of rules to guide their practice. However, as more agencies and professions begin to see the need for and develop policies for SNS use, professionals will need to assimilate these new guidelines into their practice.
Keywords: Social networking sites; Digital status; Human service professionals; Netiquette; Digital transparency and self awareness; Johari Window; Education, Technology (0710); Individual & Family Studies (0628); Social Work (0452)